Quality in the software development process in SMBs - Esponda, Silvia (2009)
The COMPETISOFT project, in which the authors of this paper participated (in the framework of the Ibero-American cooperation generated by CyTED), proposes solutions for processes and products quality assurance, considering the possibilities of small and medium businesses. Taking this project as starting point, a tool to support SMBs in the application of COMPETISOFT (basic profile) is proposed, with information regarding various issues, such as the importance of roles and their participation in the activities proposed by the model, and the generation of input and output documents for the different levels of these activities.